Therapeutic management of in-stent thrombosis after thoracic endovascular aortic repair for blunt thoracic aortic injury in a coronavirus disease 2019 patient - Karen van Rijn, BSc; Abbey Schepers, MD, PhD; Rutger W. van der Meer, MD, PhD; Carla S.P. van Rijswijk, MD, PhD; Jan van Schaik, MD; Joost R. van der Vorst, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
A 27-year-old man underwent thoracic endovascular aortic repair for blunt thoracic aortic injury. Fourteen months later, he presented with intermittent paraplegia, congestive heart failure, and a decline of kidney function as a result of high-grade aortic stenosis caused by in-stent thrombosis. He had a concurrent infection with coronavirus disease 2019. The patient was successfully treated using axillofemoral bypass, followed by stent relining 2 weeks later. The possible risk factors and the optimal therapeutic approach for in-stent thrombosis remain unknown, because only a limited number of cases describing this rare complication have been reported.